Mesoporous silica immobilized cobalt complex: an efficient catalyst for epoxides ring opening by aromatic amines under ambient conditions - Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shivaraj B. (Catalysis Communications, 2009)
{Cobalt complex, CobpbH(2)Cl(2)2H(2)O [where
Keywords: beta-Amino alcohols; CobpbH(2)Cl(2)2H(2)O complex; Epoxide ring opening; Immobilization; SBA-15

MoO3/SiO2: an efficient and selective catalyst for the synthesis 1,3-dioxolane and 1,3-dioxane - Amrute, Amol P.; Sahoo, Suman; Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shiva B. (Catalysis Communications, 2009)
A series of MoO3/SiO2 catalysts with varying amounts of MoO3 has been synthesized and the catalytic activities of these were compared with the known solid acid catalysts in the synthesis of 1,3-dioxolane. MoO3/SiO2 catalyst showed a better activity and selectivity in 1,3-dioxolane synthesis compared to the other catalysts. MoO3/SiO2 catalyst system was further successfully applied for the synthesis of 1,3-dioxanes in the Prins cyclization of olefins and formaldehyde. The proposed catalyst was thermally stable and could be recovered and reused at least in four consecutive cycles with no significant loss in the substrates conversions and products selectivities. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 1; 3-Dioxolanes; Cycloaddition; MoO3/SiO2; Prins cyclization; Sol-gel method; solid acid catalysts